Comparative and competitive adsorption of heavy metals (Cd2+, Cu2+, Ni2+, Pb2+ and Zn2+) in aqueous medium onto chitosan-montmorillionite composite beads - Buscano, Sonia Ibarra
This study synthesized a novel adsorbent by blending chitosan with montmorillionite. The adsorption properties of heavy metals viz. Cd2+, Cu2+, Ni2+, Pb2+ and Zn2+ from single and multi-ion systems in synthetic aqueous medium was investigated in a batch manner at 25 ˚C, agitattion speed of 50 rpm, solution pH 4 and in dilute quantities (5-200 mg/1). Experiments conducted were based on the intial metal concentration, absorbent loading, and crosslinking with EGDE. Evaluation of isotherms using Langmuir and Freundlich yielded a good fit with both models (R2 >0.90) signifying that the adsorption sites are non-specific and non-uniform. Adsorption mechanism followed the pseudo-second kinetic model.